2022
DOI: 10.1186/s40643-022-00504-8
|View full text |Cite
|
Sign up to set email alerts
|

Microbiomes of biohydrogen production from dark fermentation of industrial wastes: current trends, advanced tools and future outlook

Abstract: Biohydrogen production through dark fermentation is very attractive as a solution to help mitigate the effects of climate change, via cleaner bioenergy production. Dark fermentation is a process where organic substrates are converted into bioenergy, driven by a complex community of microorganisms of different functional guilds. Understanding of the microbiomes underpinning the fermentation of organic matter and conversion to hydrogen, and the interactions among various distinct trophic groups during the proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(12 citation statements)
references
References 151 publications
0
6
0
Order By: Relevance
“…The aforementioned conditions corroborate the findings of this study, which demonstrated that sucrose yielded the highest hydrogen production in comparison to the co-digestion of NG and FW. However, the involvement of lactic acid bacteria in the hydrogen production reactor is still debatable due to some findings mentioning their ability to inhibit the hydrogen production rate by competing the sugar consumption with other hydrogen-producing bacteria ( Dzulkarnain et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…The aforementioned conditions corroborate the findings of this study, which demonstrated that sucrose yielded the highest hydrogen production in comparison to the co-digestion of NG and FW. However, the involvement of lactic acid bacteria in the hydrogen production reactor is still debatable due to some findings mentioning their ability to inhibit the hydrogen production rate by competing the sugar consumption with other hydrogen-producing bacteria ( Dzulkarnain et al, 2022 ).…”
Section: Resultsmentioning
confidence: 99%
“…In biohydrogen production studies, mixed sludges are favored due to their non-stringent bioprocess requirements, as H 2 can be produced under non-sterile conditions at various conditions [ 66 ]. Furthermore, acidogenic fermentation involving the sludge is usually preferred for pilot-scale demonstrations as they are easier to operate and control than monocultures [ 67 ].…”
Section: Biofilm Enrichment Methods Applied In Biohydrogen Fermenter ...mentioning
confidence: 99%
“…Another essential genus is Enterobacter, with species such as Enterobacter aerogenes also contributing to hydrogen production under anaerobic conditions [63,232,233]. Photofermentation depends on solar energy to generate hydrogen, with phototrophic bacteria such as Rhodobacter sphaeroides and Rhodopseudomonas palustris leading this process [234][235][236]. These microorganisms work by capturing solar energy, allowing the transformation of organic substrates into hydrogen [232,235].…”
Section: Overviewmentioning
confidence: 99%
“…Photofermentation depends on solar energy to generate hydrogen, with phototrophic bacteria such as Rhodobacter sphaeroides and Rhodopseudomonas palustris leading this process [234][235][236]. These microorganisms work by capturing solar energy, allowing the transformation of organic substrates into hydrogen [232,235]. Within the fermentation environment, microbial interactions are complex and directly influence hydrogen production efficiency [44,153,185,231].…”
Section: Overviewmentioning
confidence: 99%